2018
DOI: 10.2298/vsp160620369i
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for fear of falling in the elderly in Serbia

Abstract: Background/Aim. After a fall, the elderly can develop a fear of falling which can be more frequent and more serious problem than the fall itself because it represents the main factor limiting an older person in his/her everyday functioning. The aim of this study was to identify and examine, in a more detailed way, risk factors for developing fear of falling triggered by the history of their falls over the previous year in the elderly in Serbia who live in houses or apartments. Methods. The cross-sectional stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 40 publications
1
3
0
1
Order By: Relevance
“…These factors include sociodemographic factors [23], the history of falls [24], the health status, e.g., arthritis [25], osteoporosis [26], visual problems [27], problems with urination [28], balance disorder and stroke [29], cognitive status [30], orthostatic hypotension [31]. Our results confirm these facts and suggest that many fall risk factors are directly responsible for developing the fear of falling [32].…”
Section: Discussionsupporting
confidence: 77%
“…These factors include sociodemographic factors [23], the history of falls [24], the health status, e.g., arthritis [25], osteoporosis [26], visual problems [27], problems with urination [28], balance disorder and stroke [29], cognitive status [30], orthostatic hypotension [31]. Our results confirm these facts and suggest that many fall risk factors are directly responsible for developing the fear of falling [32].…”
Section: Discussionsupporting
confidence: 77%
“…Pioneering research conducted in the Republic of Serbia on the identification of the elderly at risk of falling and the risk factor for falling (8), and risk factors for the onset of fear of falling (9) showed that age was a predictive risk factor for decline.…”
Section: Discussionmentioning
confidence: 99%
“…In the Republic of Serbia, pioneering research on the identification of older people at risk of falling (8), risk factors for falling and fear of falling (9) were conducted. In all of these studies, female gender has proved to be a predictive risk factor for falling.…”
Section: Introductionmentioning
confidence: 99%
“…Истраживања су показала да страх од пада у највећем проценту постоји код жена, особа старости између 75 година и 79 година и 80 и више година, особа које су имале више од два пада и повреде настале приликом пада, особa које су повремено и често у ситуацији "близу" пада, лица које имају проблема с видом, итд. (Ivanović, Trgovčević, 2018…”
Section: здрављеunclassified
“…Research has shown that the highest percentage of fears of falls occur with women between the ages of 75 and 79 and 80 and over, people who have had more than two falls and present injuries resulting from the fall, people who are occasionally and oft en in a situation of "near" fall, people with vision problems, etc. (Ivanović, Trgovčević, 2018) 12 .…”
Section: Healthmentioning
confidence: 99%